The Ethics of War and Peace : An Introduction - Frowe, Helen (Rawalpindi Services Book Club, 2013)
When is it right to go to war? When is a war illegal? What are the rules of engagement? What should happen when a war is over? How should we view terrorism? This book is a fresh and contemporary introduction to one of the oldest but still most relevant ethical debates. It introduces students to contemporary "just war" theory in a stimulating and engaging way, perfect for those approaching the topic for the first time. Examined are these debates: theories of self defense and national defense; Jus ad Bellum, Jus in Bello, and Jus post Bellum; the moral status of combatants; the principle of non-combatant immunity; and the nature of terrorism and the moral status of terrorists. Each chapter concludes with a useful summary, discussion questions and suggestions
Include Bibliography and Index
Keywords: Military ethics -- War--Moral and ethical aspects